EFEKTIVITAS EDUKASI AUDIO VISUAL PENCEGAHAN TEMPER TANTRUM PADA ANAK PRA SEKOLAH TERHADAP PENGATAHUAN DAN SIKAP IBU - Reza Andriani (IKesT Muhammadiyah Palembang, 2023)
ABSTRACT Introduction: Preschoolers are children who are at the level (level) before elementary school, namely kindergarten in the age range of 3-6 years. Preschool-age children often experience temper tantrums, which are uncontrolled emotional outbursts in children, which often appear in toddlers. Lack of mother's awareness and knowledge about tempered tantrums plays an important role in overcoming temper tantrum behavior in children. Methods: This study uses a quantitative approach, the method used in this study is a quasi-experimental with the type of pre-post test control group design. Results: The use of audio-visual education (video) is 1.6 times more effective than education through leaflets in increasing mother's knowledge by >20. Statistically, there was no significant difference in the mother's attitude after the intervention between the treatment and control groups p>0.05. Discussion: Providing audio-visual education about temper tantrums is an effort to prevent and deal with temper tantrums in children. Keywords: video, temper tantrum, knowledge, attitude